A TtAgo-mediated LAMP System for highly sensitive and specific detection of rotavirus in pediatric diarrheal samples - Wang, Ligong; Fan, Linlin; Wang, Dan; Ma, Qian; Hu, Jian; Wang, Xiaoqin (Frontiers in Cellular and Infection Microbiology, 2025)
Rotavirus remains a leading cause of severe pediatric gastroenteritis worldwide, particularly in regions with limited healthcare resources, timely diagnosis is essential for effective patient management and outbreak containment. Loop-mediated isothermal amplification (LAMP) offers rapid nucleic acid amplification under constant temperature, yet classic LAMP assays are prone to false positives from nonspecific amplification products. Here, we present a reverse transcription LAMP (RT-LAMP) assay integrated with Thermus thermophilus Argonaute (TtAgo)–mediated probe cleavage for highly sensitive and specific detection of rotavirus. The assay targets a conserved region of the NSP5 gene, coupling rapid isothermal amplification with programmable guide DNA–directed cleavage and fluorescence signal generation. Under optimized conditions, the system reliably detected as few as 10 copies/μL within 60 minutes, without cross-reactivity to other common viral or bacterial pathogens. In clinical testing of 60 pediatric stool samples (40 rotavirus-positive, 20 negative diagnosed by RT-qPCR), the TtAgo-mediated LAMP assay achieved 100% sensitivity and specificity, outperforming classic LAMP and antigen-based methods. Receiver operating characteristic analysis yielded an area under the curve of 1.00, compared with 0.80 for classic LAMP. These findings demonstrate that integrating TtAgo into the LAMP workflow markedly enhances diagnostic accuracy and reliability, providing a practical and laboratory-ready molecular tool for rotavirus detection.